Outcome of Surgery in both low & high Varity of VVF - Md Nasir Uddin,; Pravath Chandra Biswas,; Mohammad Abdus Salam,; Mohammad Masum Hasan,; Md Zahid Hussain,; Islam, Mohammad Rafiqul (Bangladesh Journal of Urology, 2025)
Background: VVF is a dehumanizing condition and one of the most troublesome complications of pelvic surgery, obstructed labor and malignancy in women causing increased morbidity, anxiety, disability, familial disharmony even social isolation of the patient that demand prompt , proper and special care to the patient to make them dry. Various surgical techniques have been proposed for repair of VVF, depending on the cause, location and surgeon’s experience through transabdominal and transvaginal route. Success rate of repair in both route are almost similar although morbidity in transabdominal route are more. To reduced morbidity laparoscopic surgery and Robotic surgery may be done. In our study we managed all patients with open procedure. Aims and objectives: Evaluation the success of VVF repair to make the patient dry. Methodology: Retrospective study conducted on 48 patients who underwent VVF repair with age 21-63 years mean 43 years at Dhaka Medical college Hospital, Cumilla Medical College Hospital and private clinics from January 2015- November 2024. Duration of VVF was 3 months to 2 years. Post operatively all patients underwent regular follow up. Results: In 42 cases (87.50%) cause were hysterectomy, Cesarean section were in 4 (8.33%) and obstructed labor in 2 cases (4.18%). Among 48 patients, 45 case (93.75%) were primary and 3 case (6.25%) was previous failed repair by gynecologist. No complex case was included. In 36 patients 75%) fistula were present at supratrigonal area and in 12 cases (25%) were placed at subtrigonal area. Size of fistula was less than 1 cm in 32 patients (66.66%), 1-2 cm in 12 patients (25%) and 2-3 cm in 4 patients ( 8.33%) . In 46 patients (95.33%) fistula were single and in 2 patient’s (4.16%) tract was multiple. 36 patients (75%) were operated through transabdominal approach and 12 patients (25%) through transvaginal approach. Flap was used in 5 cases (10.41%) and in 43 Cases (89.58%) flap were not used. In 3 cases (6.25%) DJ stent were used and in 45 cases (93.75%) stents were not used. 46 patients (95.83%) had successful repair. 2 patients (4.16%) had recurrence. 4 patients (8.333%) had infection, 2 patients (4.16%) developed significant hematuria and 3 patients (6.25%) developed transient incontinence of urine. Conclusion: Proper identification of fistulous tract with meticulous repair and good postoperative care make successful VVF repair. Bangladesh J. Urol. 2025; 28(1): 10-15